R&D Activity and Core Business Efficiency on the Example of Technology Companies - Tomasz L. Nawrocki (Institute of Economic Research (IER), 2015)
Taking as a basis for discussion the Schumpeter's innovation theory, this paper analyses the relationship between enterprises activity in the field of research and development and their efficiency at the core business level. This analysis was performed in two ways - with the assumption shift in time between research and development activities and companies business efficiency and without it - using the Spearman's rank correlation coefficient. The sample was accounted for 252 companies from the technology sector, whose shares are traded on NYSE or NASDAQ, and the analysis time period consisted of three years (2011-2013). Results obtained in the course of analysis generally indicate lack of strong relationship between distinguished categories. Noticeable, but only at moderate level, positive correlation was found in both considered approaches only in respect of relationship between the intensity of expenditures on research and development or y/y change of these expenditures and gross margin on sales.Therefore, it seems to be relevant to extend this research at least in such directions as: identification and characterization of factors determining efficiency of companies research and development activities, as well as examination considered relationship taking into account business diversity within the sector and wider time shift between realized research and development activities and various measures of core business efficiency.
Keywords: L25; L63; L86; O32; 330; research and development; core business efficiency; technology sector